Sarcoidosis presenting erythema nodosum-like lesions: report of two cases - Taeko Nakamura-Wakatsuki; Toshiyuki Yamamoto (Our Dermatology Online, 2013)
Introduction: Sarcoidosis is a systemic non-infectious granulomatous disorder which exhibits various specific and non-specific cutaneous manifestations. Erythema nodosum-like eruption is a rare specific lesion associated with sarcoidosis, which histologically shows non-caseating epithelioid granuloma. It is suggested that this type is frequently associated with ocular sarcoidosis.Main observations: We describe two Japanese cases presenting with erythema nodosum-like eruptions on the lower legs, which histologically showed sarcoidal granuloma. The tenderness of erythema nodosum-like eruption is milder than that of non-specific erythema nodosum. Lung involvement was observed in both cases, and ocular involvement was seen in one of them.Conclusions: Because of the high frequency of extra-cutaneous involvement, we should carry out skin biopsies to reveal specific sarcoidal granulomas appropriately and follow up patients with erythema nodosum-like eruption carefully.